The effects of the types of storytelling and deservedness of rewards on the altruistic behavior of children. - Prieto, Mary Grace G.
An experiment using a 2x2 factorial design was conducted to determine the effect of the two independent variable, types of storytelling and deservedness of reward, and the interaction of the two on the altruistic behavior of children, sixty pupils from kinder 2 to grade grade 2 of Mina Central School were the subjects of the experiment. Children were exposed to storytelling, either religious or nonreligious, and then made to feel deserving or undeserving of their reward on the task. Altruism was measured by the number of pieces of jellyace that subjects donated for a sick child who cried for candy. The analysis of variance showed that children who feel undeserving are more altruistic than the children who were made to feel deserving of their reward. No interaction effect between the storytelling and deservedness of reward's effect on altruism was found.